Susceptibility and plant immune control—a case of mycorrhizal strategy for plant colonization, symbiosis, and plant immune suppression - Enebe, Matthew Chekwube; Erasmus, Mariana (Frontiers in Microbiology, 2023)
Plants and microbes (mycorrhizal fungi to be precise) have evolved together over the past millions of years into an association that is mutualist. The plants supply the fungi with photosynthates and shelter while the fungi reciprocate by enhancing nutrient and water uptake by the plants as well as, in some cases control of soil borne pathogens. But this fungi-plant association is not always beneficial. We argue that mycorrhizal fungi, despite contributing to plant nutrition, equally increase plant susceptibility to pathogens and herbivorous pests’ infestation. Understanding of mycorrhizal fungi strategies for suppressing plant immunity, the phytohormones involved and the signalling pathways that aid them will enable the harnessing of tripartite (consisting of three biological systems) - plant-mycorrhizal fungi-microbes interactions for promoting sustainable production of crops